Green tea catechins can bind and modify ERp57/PDIA3 activity - Trnková, Lucie; Ricci, Daniela; Grillo, Caterina; Colotti, Gianni; Altieri, Fabio (Biochimica et biophysica acta, 2013)
BACKGROUND: Green tea is a rich source of polyphenols, mainly catechins (flavanols), which significantly contribute to the beneficial health effects of green tea in the prevention and treatment of various diseases. In this study the effects of four green tea catechins on protein ERp57, also known as protein disulfide isomerase isoform A3 (PDIA3), have been investigated in an in vitro model. METHODS: The interaction of catechins with ERp57 was explored by fluorescence quenching and surface plasmon resonance techniques and their effect on ERp57 activities was investigated. RESULTS: A higher affinity was observed for galloylated cathechins, which bind close to the thioredoxin-like redox-sensitive active sites of the protein, with a preference for the oxidized form. The effects of these catechins on ERp57 properties were also investigated and a moderate inhibition of the reductase activity of ERp57 was observed as well as a strong inhibition of ERp57 DNA binding activity. CONCLUSIONS: Considering the high affinity of galloylated catechins for ERp57 and their capability to inhibit ERp57 binding to other macromolecular ligands, some effects of catechins interaction with this protein on eukaryotic cells may be expected. GENERAL SIGNIFICANCE: This study provides information to better understand the molecular mechanisms underlying the biological activities of catechins and to design new polyphenol-based ERp57-specific inhibitors.
Keywords: Ligands; Models, Molecular; Enzyme Assays; Catalytic Domain; Spectrometry, Fluorescence; Humans; ligandy; povrchová plasmonová rezonance; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Protein Binding; fluorescenční spektrometrie; oxidace-redukce; enzymatické testy; lidé; Recombinant Proteins; molekulární modely; Protein Disulfide-Isomerases; proteindisulfidisomerasy; Catechin; DNA; rekombinantní proteiny; Kinetics; Surface Plasmon Resonance; katalytická doména; vazba proteinů; Oxidation-Reduction; katechin; terciární struktura proteinů; Protein Structure, Tertiary; kinetika